REKABET YASAĞI KAYDINDAN DOĞAN REKABET ETMEME BORCUNUN AYNEN İFASI (TBK m. 446/3) - (:unkn) unknown (My University, 2016)
İşveren, işçinin rekabet etmeme borcunun aynen ifasını talep edebilir. Türk Borçlar Kanunu; işverenin aynen ifa davası açabilmesini, bir dizi nitelikli koşulun gerçekleşmesi şartına bağlamıştır. Buna göre, işveren aynen ifayı talep hakkını yazılı şekilde saklı tutmalı ve işverenin ihlal edilen menfaatlerinin önemiyle işçinin davranışı, rekabet yasağı kaydına aykırı durumun ortadan kaldırılmasını haklı göstermelidir. İşveren aynen ifa davasını açmadan önce veya dava sırasında mahkemeden ihtiyati tedbir kararı isteyebilir. İşçi ilâmın gereğini yerine getirmediği takdirde, işverenin şikâyeti üzerine, icra mahkemesince tazyik hapsine mahkûm edilecektir.

The employer may demand the specific performance of employee's the non-competition duty. The Code of Obligations sets out some specific conditions for the employer who is willing to bring an action of specific performance against the employee for the enforcement of the noncompetition clause. Accordingly, the employer should reserve his right to specific performance in written form and the significance of the employer's violated interests as well as the conduct of the employee should justify the elimination of the breach of the non-competition clause. The employer may request from the court to give a preliminary injunction before proceeding or during the process. If the employee does not comply with the verdict, he shall be sentenced to a coercive imprisonment by the execution court upon the complaint by the employer.
THE SPECIFIC PERFORMANCE OF THE NON-COMPETITION CLAUSE (TURKISH CODE OF OBLIGATIONS ART. 446/3)
Keywords: Hukuk